An evaluation of practice nurses working with general practitioners to treat people with depression. - Mann, A H (1998)
BACKGROUND: The diagnosis and treatment of depression constitutes a significant component of a general practitioner's workload. A pilot study has suggested that the practice nurse may have an important contribution to make in the care of patients with depression. AIM: To evaluate an extended role for practice nurses in improving the outcome of depression through two specially-designed interviews running in parallel. METHOD: Two naturalistic, random allocation studies took place concurrently over four months. Study 1 evaluated the effectiveness of standardized psychiatric assessment by a practice nurse and feedback of information to the general practitioner (GP). Study 2 evaluated the above assessment and feedback combined with nurse-assisted follow-up care. Twenty general practices participating in the Medical Research Council General Practice Research Framework took part in the study. Subjects included general practice attenders identified as depressed by their GP. The main outcome measures were a change in Beck Depression Inventory (BDI) scores and in the proportion of patients fulfilling DSM-III criteria for major depression. RESULTS: A total of 577 patients were recruited; 516 [89% (95% CI = 86-92%)] were rated as depressed on the BDI and 474 [82% (95% CI = 79-85%)] met criteria for DSM-III major depression. Altogether, 524 (91%) patients completed follow-up at four months. All groups of patients showed improvement, but no difference in the rate of improvement was shown for the nurse intervention groups. BDI mean scores fell from 18.54 (95% CI = 17.53-20.06) to 11.53 (95% CI = 10.02-13.04) in Study 1, and from 21.01 (95% = CI 20.26-21.86) to 10.62 (95% CI = 9.73-11.51) in Study 2. The proportion of patients fulfilling criteria for DSM-III major depression in Study 1 fell from 80% (95% CI = 73-87%) to 30% (95% CI = 22-38%), and in Study 2 from 80% (95% CI = 76-84%) to 27% (95% CI = 23-31%). Prescription rates of antidepressant medication were higher than expected, ranging between 63% and 76% in the two studies. CONCLUSION: There was an increase in the rate of antidepressant prescription, but no additional benefit could be adduced for patients who received a nurse intervention.